Association of Intrathecal Immunoglobulin G Synthesis with Disability Worsening in Multiple Sclerosis - Gasperi, Christiane; Salmen, Anke; Antony, Gisela; Bayas, Antonios; Heesen, Christoph; Kümpfel, Tania; Linker, Ralf; Paul, Friedemann; Stangel, Martin; Tackenberg, Björn; Bergh, Florian Then; Warnke, Clemens; et al. (JAMA Neurology, 2019)
Importance: Reliable biomarkers associated with disability worsening in multiple sclerosis (MS) are still needed. Objective: To determine a possible association of intrathecal IgG synthesis and early disability worsening as measured by Expanded Disability Status Scale (EDSS) scoring in patients with relapsing-remitting MS or clinically isolated syndrome. Design, Setting, and Participants: Cerebrospinal fluid measurements and clinical data from the observational longitudinal German national multiple sclerosis cohort were analyzed. Patients were recruited between August 2010 and November 2015 from 18 centers. Data analysis was completed from August 2018 to December 2018. Exposure: Patients were offered standard immunotherapies per national treatment guidelines. Main Outcomes and Measures: A possible association between intrathecal IgG synthesis and risk of EDSS worsening 4 years after study inclusion was tested as the primary end point by multivariable binomial regression analysis. Kaplan-Meier analysis with a log-rank test was used to assess the association of intrathecal IgG synthesis with the time to EDSS worsening. Associations between intrathecal IgM or IgA synthesis and other cerebrospinal fluid parameters and EDSS worsening were analyzed as exploratory end points. Data collection began before the hypotheses were formulated. Results: Of all 1376 patients in the German Competence Network of Multiple Sclerosis cohort, 703 patients were excluded owing to missing cerebrospinal fluid or EDSS data. Of the 673 included patients, 459 (68.2%) were women. The mean (SD) age at baseline was 34 (10) years. Intrathecal IgG synthesis was associated with a higher risk of EDSS worsening after 4 years (odds ratio, 2.02 [95% CI, 1.15-3.58]; P =.01), independent of the occurrence of relapses and disease-modifying therapy. Additionally, intrathecal IgG synthesis was associated with earlier EDSS worsening; 4 years after study entry, worsening occurred in 28.4% (95% CI, 22.7%-34.1%) and 18.1% (95% CI, 12.4%-23.9%) of patients with and without intrathecal IgG synthesis, respectively. No association of other routine cerebrospinal fluid parameters with EDSS worsening was found. Conclusions and Relevance: Patients with new diagnoses of relapsing-remitting multiple sclerosis or clinically isolated syndrome with intrathecal IgG synthesis had a higher risk of and shorter time to EDSS worsening across a 4-year period of follow-up. Intrathecal IgG synthesis is a potentially useful marker for disability worsening in patients with multiple sclerosis and may be useful for early treatment decisions.
CRIS-Team Scopus Importer:2019-05-17